Advanced engineering mathematics - Kreyszig, Erwin. (John Wiley and Sons, 1999)
This book is about: Ordinary Differential equations; Linear algebra, vector calculus; Fourier analysis and partial differential equations; Complex analysis; Numerical methods; ...